2023
DOI: 10.1002/chem.202301014
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cu‐Substituted O3‐Type NaFe0.5Mn0.5O2 Cathode Materials for Sodium‐Ion Batteries

Abstract: O3-type Fe/Mn-based layered oxide cathode materials with abundant reserves have a promising prospect in sodium-ion batteries. However, the electrochemical reversibility of most O3-type Fe/Mn-based oxide cathode materials is still not high enough. Herein, the effect of different Cu contents on the electrochemical properties of O3-NaFe 0.50 Mn 0.50 O 2 materials is systematically investigated. The as-prepared NaFe 0.30 Mn 0.50 Cu 0.20 O 2 cathode achieves the synergistic optimization of the interface and bulk ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Zheng et al conducted an in-depth investigation into the controlled-atmosphere storage effects of O3-NaNi 0.5 Mn 0.5 O 2 , 45 a well-documented air-sensitive layered oxide known for its intricate structural degradation tendencies. 32,49 Through XRD analysis (Fig. 2a), it has been shown that O3-NaNi 0.5 Mn 0.5 O 2 experiences a phase transition from the O3 to P3 structure after 15 days of exposure to ambient air.…”
Section: Methodologies Utilized To Study Air Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Zheng et al conducted an in-depth investigation into the controlled-atmosphere storage effects of O3-NaNi 0.5 Mn 0.5 O 2 , 45 a well-documented air-sensitive layered oxide known for its intricate structural degradation tendencies. 32,49 Through XRD analysis (Fig. 2a), it has been shown that O3-NaNi 0.5 Mn 0.5 O 2 experiences a phase transition from the O3 to P3 structure after 15 days of exposure to ambient air.…”
Section: Methodologies Utilized To Study Air Degradationmentioning
confidence: 99%
“…63–65 Moreover, FTIR proves invaluable in assessing the air stability of cathode materials. 49,59,60 Since Na 2 CO 3 or NaHCO 3 tends to form on particle surfaces in an amorphous state, detecting these species through XRD proves challenging. However, FTIR proves invaluable in observing carbonate presence on the surface, especially with increased hydration levels as shown in Fig.…”
Section: Methodologies Utilized To Study Air Degradationmentioning
confidence: 99%
See 1 more Smart Citation